New low-earth orbit satellites authentication and group key agreement protocol - Zijian ZHANG; Qi ZHOU; Chuan ZHANG; Xiaoyao TONG; Chunlei LI; Long WANG (Tongxin xuebao)
Due to the function of communication and continuous monitoring,the low-earth orbit satellites are widely used in the aerospace field.However,there is no special authentication protocol in the existing satellite communication system.In order to solve this problem,a lightweight authentication protocol which considering the switch of communication path in the authentication process was designed for the low-earth orbit satellites,and the proposed protocol was verified by simulation and compared with the 3GPP AKA protocol.The simulation results show that the protocol has a 20% higher efficiency than 3GPP AKA protocol,and the spend of group key agreement protocol is about 300 ms.